CRYSTAL AND MOLECULAR STRUCTURE OF 14α-ACETOXY-13α-HYDROXYMULIN-11-EN-20-OIC ACID MONOHYDRATE - Iván Brito; Jorge Borquez; Ruben Muñoz; Alejandro Cárdenas (Journal of the Chilean Chemical Society, 2018)
The structure of this 14α-acetoxy-13α-hydroxymulin-11-en-20-oic acid monohydrate consists of a mulinane skeleton and the corresponding isopropyl, methyl, carboxyl and methyl groups at C3, C8, C5, C13, respectively, which are β-oriented, whereas the hydroxyl and acetoxy groups at C13 and C-14 are α-oriented. The cyclopentane (A), cyclohexane (B) and cycloheptene (C) rings are trans (A/B) and (B/C) cis fused, and in an envelope, chair, and twist conformation respectively. In the crystal the organic molecules are linked by the water molecules by two intermolecular OH⋅⋅⋅O hydrogen bond forming 1D-dimensional chains with graph-set notation (9).